“Closing” on Group-Centrism: A systematic meta-analysis on the relationship between the need for cognitive closure with the binding and individualizing moral foundations - Baldner, Conrad; Pierro, Antonio (Psychology Hub, 2024)
Inspired by the career of Lucia Mannetti, we conducted meta-analyses on the correlation between the need for cognitive closure and the binding moral foundations, as an aspect of group-centrism, as well as the individualizing moral foundations, which conceptually have a less clear link to group-centrism. We included all studies, indexed in either Scopus or Google Scholar, that included correlations between three self-report measures of the need for cognitive closure with either the binding or individualizing foundations. The R packages meta, metasens, and dmetar were used to conduct meta-analyses and follow-up tests. We identified a total of 26 studies (n=7136) that included eligible measures of need for cognitive closure and the binding foundations and 23 studies (n=6441) that included eligible measures of need for cognitive closure and the individualizing foundations. After controlling for heterogeneity and small sample size effects, we observed a larger adjusted effect size for the binding foundations (r=.32 [95%CI: .26;.38]) than for the individualizing foundations (r=.13 [95%CI: .052;.219]). In general, the larger effect size for the relationship between the need for cognitive closure and the binding foundations is consistent with the literature on the need for cognitive closure and group-centrism, however the elevated effects for heterogeneity and small sample size effects for the individualizing foundations should be investigated.